2009
DOI: 10.1007/978-90-481-2259-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Inhibits Human BKCa Channels

Abstract: Hydrogen sulfide (H(2)S) is produced endogenously in many types of mammalian cells. Evidence is now accumulating to suggest that H(2)S is an endogenous signalling molecule, with a variety of molecular targets, including ion channels. Here, we describe the effects of H(2)S on the large conductance, calcium-sensitive potassium channel (BK(Ca)). This channel contributes to carotid body glomus cell excitability and oxygen-sensitivity. The experiments were performed on HEK 293 cells, stably expressing the human BK(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 14 publications
4
59
2
2
Order By: Relevance
“…P O2 , (4) inhibitors of H 2 S synthesis inhibit hypoxic responses, and (5) potential sulfide donors augment the hypoxic responses. Recent studies on the mammalian carotid body Peng et al, 2010;Telezhkin et al, 2009;Telezhkin et al, 2010) and kidney (Beltowski, 2010) have supported this hypothesis and our assertion that this is a phylogenetically ancient and ubiquitous O 2 -sensing mechanism. The present study extends these observations to the fish GI tract and supports the hypothesis that O 2 -dependent H 2 S metabolism is a fundamental oxygen-sensing mechanism.…”
Section: R a Dombkowski And Otherssupporting
confidence: 78%
See 1 more Smart Citation
“…P O2 , (4) inhibitors of H 2 S synthesis inhibit hypoxic responses, and (5) potential sulfide donors augment the hypoxic responses. Recent studies on the mammalian carotid body Peng et al, 2010;Telezhkin et al, 2009;Telezhkin et al, 2010) and kidney (Beltowski, 2010) have supported this hypothesis and our assertion that this is a phylogenetically ancient and ubiquitous O 2 -sensing mechanism. The present study extends these observations to the fish GI tract and supports the hypothesis that O 2 -dependent H 2 S metabolism is a fundamental oxygen-sensing mechanism.…”
Section: R a Dombkowski And Otherssupporting
confidence: 78%
“…the 'O 2 sensor' . Evidence for this mechanism has been found in systemic and respiratory vascular smooth muscle Olson et al, 2008a;, urinary bladder smooth muscle , chromaffin cells (Perry et al, 2009) and O 2 -sensing chemoreceptor cells Olson et al, 2008b;Peng et al, 2010;Telezhkin et al, 2009;Telezhkin et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…2B) (60,139). In the carotid body, it has been proposed that hypoxia inhibits constitutive CO production by hemeoxygenase 2 (HO-2), which then relieves the heretofore tonic inhibitory effect of CO on cystathionine c-lyase (CSE) and H 2 S levels increase, closing largeconductance Ca 2 + -dependent K + channels (BK Ca ) (87,162,163) or TWIK-related acid-sensitive potassium (TASK) (15) channels. This depolarizes glomus cells and releases neurotransmitter.…”
Section: H 2 S and O 2 Sensingmentioning
confidence: 99%
“…5B) (87,162,163) or TASK channels (15). Li et al (87) showed that in whole cell recordings of mouse glomus cells, both hypoxia and H 2 S inhibited BK Ca channels and AOA could inhibit the hypoxic affect.…”
Section: Olsonmentioning
confidence: 99%
See 1 more Smart Citation